Receiving to the sacrament penitence and admitting the Holy Eucharist according to canon law - JANCZEWSKI, ZBIGNIEW (Prawo Kanoniczne, 2017)
In the Codex of Canon Law we read: once admitted to the blessed Eucharist, each of the faithful is obliged to receive holy communion at least once a year. This precept must be fulfilled during paschal time, unless for a good reason it is fulfilled at another time during the year. And also: All the faithful who have reached the age of discretion are bound faithfully to confess their grave sins at least once a year. This article is about if always a faithful before communion are bound to confess, in kind and in number, all grave sins committed after baptism, and which have not been confessed in an individual confession. The first part of article is about history of this problem, the second - individual and integral confession and absolution before admitting to the blessed Eucharist according to Codex of Canon Law. Next parts of article are about confession after general absolution and babies confession before their first holy communion.